The topographical-anatomical relationships of the liver, spleen and pancreas under normal and in chronic pancreatitis. - Kim, D.; Abubakirov, R. E.; Zarishnyak, N. V. (Морфологія / Morphologia / Morfologìâ, 2012)
In this study,conducted on a computer tomograph«Philips BrillianceCT16-slice» software«Brilliance Workspace»examinedtopographicanatomicalrelationshipof the liver,spleen and pancreasof 30 volunteers in thenormal(controlgroup)and 30 patients with chronicpancreatitis(experimental group) in remission and the durationof the disease from1 yearto 5yearsof agefrom 33to 76 years.Topographyof the pancreas, liver, and spleenin patientsof the experimental groupdid not differfrom thoseof control.The patientsof the experimental grouppancreasin most caseswasS-shaped, with a simultaneous increase inthe lengthandthe angle betweenthe head and thebodyin the horizontal plane, which may predisposing factorin the developmentof chronic pancreatitis.